PEMENUHAN KEBUTUHAN BERIBADAH PENGHUNI LEMBAGA PEMASYARAKATAN : SEBUAH STUDI FENOMENOLOGI - chrisyen damanik (Jurnal Medika : Karya Ilmiah Kesehatan, 2018)
Prison inmates are someone who is serving a sentence for a criminal act or conviction. As individuals, prisoners have the same needs as other humans in general, such as biological needs, spiritual and social needs. Particularly spiritual religious needs are activities that are often carried out by each individual, but cannot be done due to the loss of individual freedom. Objective: to explore the meaning of Lapas residents' experience in meeting worship needs. Method: this study used a phenomenological approach conducted in June 2018. Data was collected through interviews with 5 participants. Results: the results of interviews with 5 participants resulted in 2 themes 1) worship activities carried out by participants both facilitated by prisons and worship conducted by themselves 2) participants felt calm and improved themselves better in interpreting worship and expecting sustainability after being free. Conclusion: based on the results of the study it can be concluded that prison residents feel self-improvement in interpreting worship by attending worship services held by prisons and hoping to continue after being released from prison. calmness.